Strategi Komunikasi Pondok Pesantren Nurul Iman Desa Ujung Tanjung Dalam Menanamkan Nilai-Nilai Akhlak Kepada Santri - rati hafsa sari; Aliasan Aliasan; Ahmad Harun Yahya (Tabayyun: Journal of Journalism, 2023)
ABSTRACT Islamic boarding schools have a significant role in religious education institutions whose existence is continuously needed to foster adjustments or improvements in behavior in Tazkiyatun Nafs (purification of the heart) and self-approach to Allah SWT. The purpose of this study was to find out how the interaction of Islamic boarding schools with students in developing their values at the Nurul Iman Islamic boarding school, Ujung Tanjung Village. This study was conducted to clarify the communication plan for the Nurul Iman Islamic Boarding School in Ujung Tanjung Village. Because it is a religious organization that offers education, the authors choose the Nurul Iman Islamic Boarding School. Having a vision, mission, and goals as an Islamic educational institution engaged in education, and to achieve these goals the Nurul Iman Islamic Boarding School uses an effective communication strategy, therefore a thesis written by the author entitled "Nurul Iman Village Islamic Boarding School “Communication Strategy Ujung Tanjung in Instilling Moral Values in Santri” is used to find out the communication strategy used by Nurul Iman Islamic Boarding School. The method used in this research is descriptive qualitative method, the data is collected by means of interviews, documentation and observation. Keywords: Communication Strategy, Instilling Moral Values, Santri Morals